Predictors of beliefs in the evaluation process of educational actions to the health team - Gabriela Cristina Costa Gonçalves; Daniela Miori Pascon; Melissa Messias; Patrícia Tavares dos Santos; Everson Cristiano de Abreu Meireles; Vera Lucia Mira (Universidade Federal de Santa Maria, 2019)
Aim: to evaluate the dimensionality and internal consistency of the belief scale; to verify the existence of relations between criterion variables and belief variables; to investigate predictive variables of beliefs in the evaluation process of educational actions of the health team. Method: quantitative correlational study developed in 14 health institutions, with the participation of 992 workers, in which a Likert scale was applied, consisting of 31 items related to the team beliefs in the training evaluation process. The dimensionality/internal structure of the scale was carried out by means of exploratory factorial analyses; standard multiple regression analyses, Student t tests, ANOVA and post hoc analyses were also applied. Results: three factors were found; the predictive variables were "number of trainings in the last 12 months", "participation in training at the time of the research" and "age".Conclusions: the scale presented internal consistency and there was identification of correlations and predictive variables.